1 Real world experience in treating chronic hepatitis C with direct acting antivirals (DAAS) in northern ireland. (5th April 2017) - McCaughan, H; Stratton, L; Patterson, K; McCormick, O; Wasson, G; Cadden, I; Cash, J; McCorry, R; McDougall, N
Abstract : Background: Oral direct acting antiviral (DAA) treatments for hepatitis C virus (HCV) have emerged in recent years and show excellent results regarding side effects and clearance of the virus (defined as negative HCV PCR 12 weeks after completion of therapy or SVR12). Aim: To assess response to new DAAs in Northern Ireland according to genotype, presence of cirrhosis, and previous treatment. Method: Treatment outcomes were reviewed for all patients treated with a DAA for chronic HCV in Northern Ireland from March 2015 until July 2016. Results: 105 treatments were given to 104 patients (1 patient treated twice) - 68 males, 41 cirrhotic, and 67 with previous treatment failure. Genotype prevalence is shown in Fig 1 . 89 received all oral DAA therapy (44 Abbvie product, 28 Harvoni+/- ribavirin, 15 sofosbuvir/daclatasvir/ribavirin) and 16 received sofosbuvir + Peg interferon + ribavirin. Overall 100 (95%) treatments were successful and achieved SVR 12. Three patients (all cirrhotic genotype 1 with prior treatment failure) stopped treatment (Abbvie) within 3 weeks due to decompensation, one of whom achieved SVR12 with subsequent treatment. 1 patient failed with sof/peg/riba and 1 patient failed to attend for SVR12 check (negative at end of treatment). Conclusions: In our experience, all-oral DAA therapy is highly efficacious provided patients can complete the course. Caution is required with cirrhotic patients even if well compensated before treatment.